Key Parameters for the Analysis Stage of Internationalization of Operations - Grillo, Hanzel; Mula, Josefa; Martínez, Sandra; Errasti, Ander (Brazilian Journal of Operations & Production Management, 2018)
In this paper, we identify the key parameters to consider in a decision model on internationalization of operations. In order to propose these parameters, the GLOBOPE framework was adopted as the basis of this work. This framework contemplates the three commonest challenges of global operations configuration for industrial manufacturing companies in an internationalization process, which are: new facility implementation (NFI); global suppliers’ network development (GSND); multisite production network configuration. A set of suitable parameters is herein provided for NFI and GSND in the analysis stage from strategic, tactical and operational decision levels. These parameters could be used in the future as a basis for the development of quantitative tools for decision making on the internationalization of operations.